Alternate Currents in Women's Republicanism During the French Revolution. Issue 4 (2nd October 2019) - Ball, Patrick
ABSTRACT: In this article I consider alternate but often complementary models for women's republicanism from those discussed by Sandrine Bergès. In particular, I make use of Bergès's insights about extending philosophical inquiry beyond traditional texts to analyse how militant political action was both informed by and informed the creation of philosophical texts, and consider the possibility of bringing direct action into the realm of philosophical investigation.